2017
DOI: 10.1007/s11252-017-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Canopy precipitation interception in urban forests in relation to stand structure

Abstract: Urban forests provide important ecosystem services. In terms of hydrological benefits, forest ecosystems in urban environments represent qualitative and quantitative filter for rainwater. We quantified the canopy interception in relation to urban forest stand structure and rainfall intensity in an urban transect of the mixed (upland) forest in the city centre, towards a riparian pine forest and a floodplain hardwood forest in the City of Ljubljana, Slovenia. Bulk precipitation in open areas and throughfall wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 76 publications
0
26
1
4
Order By: Relevance
“…For example, Chen et al [32] and Alan and Ali [35] reported that the canopy interception ratio was inversely proportional to the rainfall intensity. Kermavnar and Vilhar [36] found that seasonal variation in canopy interception was due to different rainfall intensities. However, Li et al [37] and Peng et al [38] found that the rainfall intensity had no significant effect on canopy interception.…”
Section: Effects Of Rainfall Properties On Canopy Interceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Chen et al [32] and Alan and Ali [35] reported that the canopy interception ratio was inversely proportional to the rainfall intensity. Kermavnar and Vilhar [36] found that seasonal variation in canopy interception was due to different rainfall intensities. However, Li et al [37] and Peng et al [38] found that the rainfall intensity had no significant effect on canopy interception.…”
Section: Effects Of Rainfall Properties On Canopy Interceptionmentioning
confidence: 99%
“…Some studies found that the canopy interception amount was significantly associated with the maximum rainfall intensity within the first 30 min rather than with the average rainfall intensity [39]. And several studies have reported that rainfall intensity did not have an evident impact on canopy interception in some forest types [36,40]. Therefore, whether there is an impact of rainfall intensity on canopy interception or not is still on debate.…”
Section: Effects Of Rainfall Properties On Canopy Interceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous research of canopy interception mainly tackles the impact of rainfall on canopy interception of plants [11][12][13]. Many scholars [14][15][16][17] proved that the water loss of forest ecosystem is partially attributable to the rainfall loss caused by canopy interception and the subsequent atmospheric evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…They cover master's theses and scientific papers mainly published by authors associated with the Faculty of Civil and Geodetic Engineering, University of Ljubljana and Slovenian Forestry Institute. The majority dealt with the effects of urban forests or urban trees in built environment, such as surface runoff [127][128][129][130][131][132][133] or quality of groundwater [134]. Thus, the hydrological aspect of urban forests seemed to be the most important.…”
Section: Resultsmentioning
confidence: 99%